Horský penzion v KÚ Karolinka - Skopalová, Vendula (Vysoké učení technické v Brně. Fakulta stavební, 2019)
Předmětem diplomové práce je návrh a zpracování stavebně technické části projektové dokumentace pro realizaci novostavby horského penzionu v Karolince s ubytovací kapacitou 36 osob. Objekt se nachází ve svahu, je podsklepen, má 2 podzemní podlaží a 3 nadzemní podlaží. Objekt je zastřešen sedlovou střechou s betonovou střešní krytinou. Svislé nosné konstrukce jsou tvořeny ze systému Porotherm. Kromě vlastního projektu je součástí i architektonická studie, požární zpráva a tepelně technické posouzení domu.

The subject of the diploma thesis is the design and process of the construction-technical part of the project documentation for realization of the new building of the mountain guest-house house in Karolina with an accommodation capacity of 36 people. The building is located on a slope, it is a basement, it has 2 underground floors and 3 aboveground floors. The building is roofed with a saddle roof with a concrete roofing. Vertical support structures are made from the Porotherm system. In addition to the project, an architectural study, a fire report and a thermal-technical assessment of the house are also included.
Mountain guest-house in Karolinka
Keywords: Sedlová střecha; penzion; hory; Porotherm; vikýř.; A saddleback roof; mountain; guest-house; skylight; Porotherm.